Delphi Method in Analyzing of Minimum Wage Setting in Indonesia: Formula vs. Negotiation Model (JEJAK: Jurnal Ekonomi dan Kebijakan, 2023)
Many countries set their minimum wages based on two models, through negotiation or mathematical formulas. In Indonesia, the negotiation model has been used to determine the minimum wages since 2003. In 2015, the law introduced the simple formula model that was further revised in 2016 with additional variables. Using the Delphi method, this study aims to find experts’ consensus regarding whether the governance of the formula model is superior to that of the negotiation model in terms of transaction cost minimization. Using the transaction cost economics approach, the two governances were compared in their performance in facilitating the negotiation,  coordination, and dispute prevention between employ-ers and workers. This study finds that most experts reached a consensus, claiming that the mathematical formula model is more efficient than the negotiation model. In addition, most of the experts argue that data from the Central Statistic Agency (BPS) and the elimination of the role of regional heads increase the efficiency of the formula model. However, no consensus was reached regarding whether the mathematical formula can outperform the negotiation model in minimizing the risk of future disputes.